Resting Energy Expenditure in Anorexia Nervosa: Measured versus Estimated - Marwan El Ghoch; Marta Alberti; Carlo Capelli; Simona Calugi; Riccardo Dalle Grave (Journal of Nutrition and Metabolism)
Introduction. Aim of this study was to compare the resting energy expenditure (REE) measured by the Douglas bag method with the REE estimated with the FitMate method, the Harris-Benedict equation, and the Müller et al. equation for individuals with BMI < 18.5 kg/m2 in a severe group of underweight patients with anorexia nervosa (AN). Methods. 15 subjects with AN participated in the study. The Douglas bag method and the FitMate method were used to measure REE and the dual energy X-ray absorptiometry to assess body composition after one day of refeeding. Results. FitMate method and the Müller et al. equation gave an accurate REE estimation, while the Harris-Benedict equation overestimated the REE when compared with the Douglas bag method. Conclusion. The data support the use of the FitMate method and the Müller et al. equation, but not the Harris-Benedict equation, to estimate REE in AN patients after short-term refeeding.